Cosmetics - Butler, Hilda (Poucher's perfumes, cosmetics and soaps)
The first edition of this work was written by W.A. Poucher in 1923. His aim was to produce a comprehensive coverage of products giving simple background theories with basic formulations and their methods of manufacture. This new edition follows in this tradition and maintains the simplicity of approach aimed at students or specialists in one discipline, with some knowledge of science, who need an introduction to cosmetic science and technology. In the 17 years since the publication of the last edition, cosmetic science has developed to such an extent that men and women working in research and the industry, specialize in different disciplines and selected product categories, therefore each chapter has been written by specialist authors. Part 1 deals with products in alphabetical order, following previous editions. In the respective chapters, an outline of the biology and function of the skin and its appendages, ie hair, teeth and nails, is given, followed by descriptions of the needs for products, their formulation and manufacture. In Part 2 there are seven chapters covering the knowledge required and the procedures to follow when marketing cosmetics. They are analytical methods, efficacy testing, emulsion theory, microbial control, legislation, safety and stability. Part 3 contains three chapters covering historical background, the perfuming of products and lastly the psychology of fragrance. This book provides a basic knowledge of "cosmetics" - a word which covers any product used to cleanse, protect or adorn the human body. It aims to serve as a valuable introduction and source of reference for all those involved in the cosmetics and toiletries industry, including suppliers of raw materials, manufacturers of finished products, R&D laboratories in industry and educational institutions as well as beauty clinics and schools.